DISEMINASI KAJIAN FISKAL REGIONAL (KFR) SEBAGAI UPAYA PENINGKATAN LITERASI FISKAL DI PROVINSI JAMBI MELALUI KOLABORASI UNIVERSITAS DINAMIKA BANGSA DAN KANWIL DJPB PROVINSI JAMBI - Yossinomita; Herry Mulyono; Setiawan Assegaff; Akwan Sunoto; Maria Rosario; Ahmad Hussaein; Effiyaldi; Roby Setiawan; Ayu Feranika; Laura Prasasti; Eddy Suratno; Johni Paul Karolus Pasaribu; Rista Aldilla Syafri; Hanan Laras Sabrina; Mardiana R.; Abdul Rahim; Andi Nurul Izzah; Putri Indri Fitria Ningrum; Tunas Agung Jiwa Brata; Asyep Syaefudin; Junaidi (LPPM ITB AAS Indonesia Surakarta, 2025)
This community service activity aims to enhance fiscal literacy and understanding of state financial policies among stakeholders, the academic community, and students in Jambi Province through the Dissemination of the Regional Fiscal Study (Kajian Fiskal Regional/KFR) for the Third Quarter of 2025. This activity represents the implementation of a collaborative partnership between Universitas Dinamika Bangsa (UNAMA) and the Regional Office of the Directorate General of Treasury (Kanwil DJPb) of Jambi Province in supporting the comprehensive and sustainable dissemination of fiscal policy information. The materials delivered included an overview of the fiscal performance of the State Budget (APBN) and the Regional Budget (APBD) of Jambi Province presented by the Head of the Regional Office of the Directorate General of Treasury of Jambi Province, as well as a thematic analysis of the Three Million Houses Program and the Housing Financing Liquidity Facility (Fasilitas Likuiditas Pembiayaan Perumahan/FLPP) policy in Jambi Province delivered by a Local Expert from the Regional Office of the Directorate General of Treasury of Jambi Province. The activity was conducted through presentations, interactive discussions, and question-and-answer sessions involving representatives from local governments, vertical agencies, financial authorities, academics, and stakeholders in the housing sector. The results indicate an improvement in participants’ understanding of regional fiscal conditions, the synergy between the APBN and APBD, and the implications of national housing policies for regional economic development. This activity is expected to strengthen cross-sectoral coordination and support evidence-based fiscal policymaking in Jambi Province.